Пошаговое объяснение:
а.) 7х-11=10х+16
7х-10х=16+11
-3х=27
х = 27:(-3)
х = -9
Ответ: х = -9
б.)
![\frac{2x + 20}{24} = \frac{x + 12}{15} \frac{2x + 20}{24} = \frac{x + 12}{15}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2x%20%2B%2020%7D%7B24%7D%20%20%3D%20%20%5Cfrac%7Bx%20%2B%2012%7D%7B15%7D%20)
15(2х+20)=24(х+12) | :3
5(2х+20)=8(х+12)
10х+100=8х+72
10х-8х=72-100
2х=-28
х = - 28 : 2
х = - 14
Ответ: х= -14
в.) 3 + 11х = 20,5 + 16х
11х - 16х = 20,5 - 3
- 5х = 17,5
х = 17,5 : (-5)
х = - 3,5
Ответ : х = - 3,5
г.) 0,4(6х-7) = 0,5 (3х +7)
2,4х - 2,8 = 1,5х + 3,5
2,4х-1,5х=3,5+2,8
0,9х = 6,3
х = 6,3 : 0,9
х = 7
Ответ: х=7
д.)
![\frac{1}{4} - \frac{1}{3} x = 4 \frac{1}{4} - 3x \frac{1}{4} - \frac{1}{3} x = 4 \frac{1}{4} - 3x](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B4%7D%20%20-%20%20%5Cfrac%7B1%7D%7B3%7D%20x%20%3D%204%20%5Cfrac%7B1%7D%7B4%7D%20%20-%203x)
![- \frac{1}{3} x + \frac{3}{1} x = 4 \frac{1}{4} - \frac{1}{4} - \frac{1}{3} x + \frac{3}{1} x = 4 \frac{1}{4} - \frac{1}{4}](https://tex.z-dn.net/?f=%20-%20%20%5Cfrac%7B1%7D%7B3%7D%20x%20%2B%20%20%5Cfrac%7B3%7D%7B1%7D%20x%20%3D%204%20%5Cfrac%7B1%7D%7B4%7D%20%20-%20%20%5Cfrac%7B1%7D%7B4%7D%20)
![\frac{ - 1 + 9}{3} x = 4 \frac{ - 1 + 9}{3} x = 4](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20-%201%20%2B%209%7D%7B3%7D%20x%20%3D%204)
![\frac{8}{3} x = 4 \frac{8}{3} x = 4](https://tex.z-dn.net/?f=%20%5Cfrac%7B8%7D%7B3%7D%20x%20%3D%204)
![8x = 4 \times 3 8x = 4 \times 3](https://tex.z-dn.net/?f=8x%20%3D%204%20%5Ctimes%203)
![8x = 12 8x = 12](https://tex.z-dn.net/?f=8x%20%3D%2012)
![x = 12 \div 8 x = 12 \div 8](https://tex.z-dn.net/?f=x%20%3D%2012%20%5Cdiv%208)
![x= 1 \frac{1}{2} x= 1 \frac{1}{2}](https://tex.z-dn.net/?f=x%3D%20%201%20%20%5Cfrac%7B1%7D%7B2%7D%20)
Ответ: х = 1,5